Loss of TDP-43 function contributes to genomic instability in amyotrophic lateral sclerosis - Fang, Minggang; Deibler, Sara K.; Nana, Alissa L.; Vatsavayai, Sarat C.; Banday, Shahid; Zhou, You; Almeida, Sandra; Weiss, Alexandra; Brown, Robert H.; Seeley, William W.; Gao, Fen-Biao; Green, Michael R. (Frontiers in Neuroscience, 2023)
A common pathological hallmark of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) is the cytoplasmic mislocalization and aggregation of the DNA/RNA-binding protein TDP-43, but how loss of nuclear TDP-43 function contributes to ALS and FTD pathogenesis remains largely unknown. Here, using large-scale RNAi screening, we identify TARDBP, which encodes TDP-43, as a gene whose loss-of-function results in elevated DNA mutation rate and genomic instability. Consistent with this finding, we observe increased DNA damage in induced pluripotent stem cells (iPSCs) and iPSC-derived post-mitotic neurons generated from ALS patients harboring TARDBP mutations. We find that the increase in DNA damage in ALS iPSC-derived neurons is due to defects in two major pathways for DNA double-strand break repair: non-homologous end joining and homologous recombination. Cells with defects in DNA repair are sensitive to DNA damaging agents and, accordingly, we find that ALS iPSC-derived neurons show a marked reduction in survival following treatment with a DNA damaging agent. Importantly, we find that increased DNA damage is also observed in neurons with nuclear TDP-43 depletion from ALS/FTD patient brain tissues. Collectively, our results demonstrate that ALS neurons with loss of nuclear TDP-43 function have elevated levels of DNA damage and contribute to the idea that genomic instability is a defining pathological feature of ALS/FTD patients with TDP-43 pathology.